IOT-BASED EARTHQUAKE WARNING SYSTEM DEVELOPMENT AND EVALUATION - KARACI, Abdulkadir (Mugla Sitki Kocman University, 2018)
In this study a low cost earthquake warning system has been developed that will detect non-destructive foreshocks. The developed system is an IOT application where objects communicate with each other. Arduino mega was used as the micro controller in the system. The purpose of developing earthquake warning system is to announce the information about the beginning and end of the earthquake at the instant of earthquake as a tweet in tweeter and to give audible alert for the persons in the environment. IMU and piezo vibration sensors were used to detect the vibrations at the moment of the earthquake. Also, ESP8266 Wi-Fi module was included in the system for the system to connect to the internet. The system evaluates the data from IMU and vibration sensors to detect the earthquake. For IMU sensor, data is evaluated in two axes; namely x and y. ıf the change in x- or y-axis is equal to or greater than 10 or the data from vibration sensor is greater than 694 then the earthquake warning system is triggered. As a result of this triggering the system connects to internet via Wi-Fi module, a tweet is sent to inform that the earthquake has started and audible alert is given locally. ThingSpeak IoT analytics platform is used for the system top send tweet. When the system is triggered, necessary data is sent to the ThingSpeak platform and tweet is sent through this platform. Also, system’s sensitivity threshold values can be changed and adjusted. According to the results of real-time operation, it has been determined that the developed system can detect the earthquake successfully and sensitively and provide audible alert and send tweet for warning.